KESADARAN SEJARAH PESERTA DIDIK DALAM PEMBELAJARAN SEJARAH (Studi Naturalistik Inkuiri di SMAN 7 Bandung) - Anggit, - (2020)
This research is based on historical learning problems at SMAN 7 Bandung, which considers history to be sufficiently known. The objects in this study are four classes of IPS program. The problems in this study are: First, how do teachers plan history learning related to the historical awareness of students in class XI IPS SMAN 7 Bandung ?. Second, how is historical awareness developed in the history learning process related to historical awareness of students in class XI IPS SMAN 7 Bandung?. Third, how are the forms of students' historical awareness in learning history in class XI IPS SMAN 7 Bandung?. The method used in this study is the naturalistic method of inquiry. Data collection techniques in this study include observation, field notes, interviews and documents. The results of study as: First, the teacher has prepared the plan into the learning implementation plan and selected a learning method and approach that is relevant to the material related to historical awareness. Second, in the history learning process the teacher runs it according to the planning procedures that have been developed by the teacher. Third, the forms of historical awareness raised by students in the form of 1) students can live up to the meaning and nature of history, 2) students can know themselves and their people, 3) maintain the heritage of the nation's history, 4) understand and study any changes that occur 5) Learners' Historical Awareness of Contemporary Social Problems Keywords: Historical Awareness, History Learning, Naturalistic Inquiry